Artificial Intelligence and Technological Evolution: A Comprehensive Analysis of Modern Challenges and Future Opportunities - Amiri, Ghulam Ali; Hakimi, Musawer; Rajaee, Sayed Mohammad Kazim; Hussaini, Mohammad Fawad (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The rapid evolution of AI and the associated technological developments have opened up society to new opportunities and challenges that were hitherto unexplored in many fields. The impact of AI extends to technological progress and influences industry practices, socio-cultural norms, and global economic landscapes. Purpose. The paper reviews how contemporary challenges and future opportunities for AI interlink with the more extensive process of technological evolution. The paper tries to illuminate how AI technologies can be powerful and influential in the face of transforming industries, societal norms, and the technical landscape, as well as highlighting the risks and challenges that these developments could give rise to. Method. This will be based on an in-depth review of all peer-reviewed journals, case studies, and industry reports relating to AI between 2019 and 2024. Some key trends identified from the analysis in AI implementation across major sectors, including healthcare, finance, and education, have been recognized. The review is done considering the ethical, regulatory, and technical issues surrounding AI as it seeks to integrate into society Results: AI has become one of the most powerful shapers of several sectors in terms of pushing both innovation and efficiency. At the same time, it also brings substantial challenges regarding data privacy, algorithmic bias, and robust regulatory frameworks with itself. The results therefore bring out this dual nature of AI as a driver of progress and a source of intricate ethical and technical dilemmas. Conclusion. Thus, the outcome of the study is that even though AI holds immense potential for positive societal impact, its integration has to be managed by strong strategies reducing risks and maximize benefits. Interdisciplinary collaboration and adaptive policies will indeed be necessary for negotiating the fast-changing landscape of artificial intelligence and for its responsible, beneficial use in the future.